Conjunctival Inflammatory Gene Expression Profiling in Dry Eye Disease: Correlations With HLA-DRA and HLA-DRB1 - Kessal, Karima; Liang, Hong; Rabut, Ghislaine; Daull, Philippe; Garrigue, Jean-Sébastien; Docquier, Mylene; Melik Parsadaniantz, Stéphane; Baudouin, Christophe; Brignole-Baudouin, Françoise (Frontiers in immunology, 2018)
In several multicenter clinical trials, HLA-DR was found to be a potential biomarker of dry eye disease (DED)'s severity and prognosis. Given the fact that HLA-DR receptor is a heterodimer consisting in an alpha and a beta chain, we intended to investigate the correlation of inflammatory targets with the corresponding transcripts, and , to characterize specific targets closely related to HLA-DR expressed in conjunctival cells from patients suffering from DED of various etiologies. A prospective study was conducted in 88 patients with different forms of DED. Ocular symptom scores, ocular-staining grades, tear breakup time (TBUT) and Schirmer test were evaluated. Superficial conjunctival cells were collected by impression cytology and total RNAs were extracted for analyses using the new NanoString nCounter technology based on an inflammatory human code set containing 249 inflammatory genes. Two hundred transcripts were reliably detected in conjunctival specimens at various levels ranging from 1 to 222,546 RNA copies. Overall, from the 88 samples, 21 target genes showed a highly significant correlation ( > 0.8) with and and presenting the highest correlation ( = 0.9). These selected targets belonged to eight family groups, namely interferon and interferon-stimulated genes, tumor necrosis factor superfamily and related factors, Toll-like receptors and related factors, complement system factors, chemokines/cytokines, the RIPK enzyme family, and transduction signals such as the STAT and MAPK families. We have identified a profile of 21 transcripts correlated with expression, suggesting closely regulated signaling pathways and possible direct or indirect interactions between them. The NanoString nCounter technology in conjunctival imprints could constitute a reliable tool in the future for wider screening of inflammatory biomarkers in DED, usable in very small samples. Broader combinations of biomarkers associated with HLA-DR could be analyzed to develop new diagnostic approaches, identify tighter pathophysiological gene signatures and personalize DED therapies more efficiently.